2020
DOI: 10.31686/ijier.vol8.iss3.2208
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Market Focus Planning Strategies on Competitiveness of Private Universities in Nairobi County, Kenya

Abstract: In the last three decades, the republic of Kenya has witnessed a tremendous increase in the number of chartered universities and a stiff competition for students. The student enrolment base coupled with the emergence of private university education providers turned the university arena in Kenya into a student enrolment market, leading to intense competition between Public and Private Universities. The researcher realizes that, the existing studies relate competitiveness with performance. Thus, the purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 3 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…(Kinyanjui & Juma, 2014;Muoki & Okibo, 2016;Waithaka, 2017;Omuse, et al, 2018) studies found that public universities suffer resource constraints and lack vital facilities to support learning. Studies by Nderitu et al, 2018;Ndichu, (2014) focused on influence strategy on performance and effect of differentiation on competitiveness. There is scanty literature on private chartered universities in Kenya.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…(Kinyanjui & Juma, 2014;Muoki & Okibo, 2016;Waithaka, 2017;Omuse, et al, 2018) studies found that public universities suffer resource constraints and lack vital facilities to support learning. Studies by Nderitu et al, 2018;Ndichu, (2014) focused on influence strategy on performance and effect of differentiation on competitiveness. There is scanty literature on private chartered universities in Kenya.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Porter (1985) asserts that there are basic businesses strategies -differentiation, cost leadership, and focus -and a company performs best by choosing one strategy on which to concentrate. Many researchers are however of the divergent view that a combination of these strategies may offer a company the best chance to achieve a competitive advantage (Adimo, 2018;Kettunen, 2014;Nderitu et al, 2018;Wakhu & Bett, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations